2006
DOI: 10.1128/iai.00169-06
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acids Enhance Invasiveness of Cryptosporidium spp. into Cultured Cells

Abstract: Bile salts such as sodium taurocholate (NaTC) are routinely used to induce the excystation of Cryptosporidium oocysts. Here we show that NaTC significantly enhanced the invasion of several cultured cell lines by freshly excysted Cryptosporidium parvum and Cryptosporidium hominis sporozoites. A variety of purified bile salts or total bile from bovine also enhanced the invasion of cultured cells by C. parvum. Further studies demonstrated that NaTC increased protein secretion and gliding motility of sporozoites, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 32 publications
(45 reference statements)
4
28
0
3
Order By: Relevance
“…Excystation in the presence of both bile salt and Caco2 cells, however, was significantly better than in samples containing cells only. Bile salts may have a separate major role in parasite infection by activating sporozoite gliding required for host cell invasion (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excystation in the presence of both bile salt and Caco2 cells, however, was significantly better than in samples containing cells only. Bile salts may have a separate major role in parasite infection by activating sporozoite gliding required for host cell invasion (8).…”
Section: Discussionmentioning
confidence: 99%
“…Both raised temperature and acidic conditions have been demonstrated to increase the permeability of the oocyst wall to small molecules (20). It has been established that bile salts increase the rate of excystation, and a study reported that, in addition, sodium deoxycholate improved the invasiveness of sporozoites for epithelial cells (8). Increased parasite protease activity during excystation has been described, and sporozoite release was hindered by protease inhibitors (9).…”
mentioning
confidence: 99%
“…Subconfluent HCT-8 monolayers seeded in T75 flasks were infected with C. parvum oocysts at a 1:4 oocyst/host cell ratio and incubated for 24 h. This time point was chosen because at later time points monolayer perturbance increases. Taurocholic acid at a concentration of 0.05% was added with the oocysts to promote infection (11). After incubation, cell monolayers were recovered by treatment with Accutase (Innovative Cell Technologies, Inc.) and immunofluorescently labeled as described previously (31), except that polyclonal rabbit antibody specific for C. parvum sporozoites and oocysts was used as the primary antibody and the host cell membrane was not permeabilized.…”
Section: Methodsmentioning
confidence: 99%
“…However, progress in research on these organisms has been hampered by the limitations of current experimental models (6). Because animal models are suboptimal for some human infections, human colonic cell lines have been used as an alternative to study intestinal pathogens (7,8). The utility of cell lines is limited by the fact they are not derived from the small intestine and are transformed.…”
mentioning
confidence: 99%